Quantum simulation of the adsorption of toxic gases on the surface of borophene - Tạ, Thị Lương (2020)
2D materials have attracted significant research interest due to their excellent characteristics. Borophene, a new member of the 2D material family, was proven that it has a unique structure and promising properties by both empirical and theoretical studies. In this study, the adsorption configuration, adsorption energy of toxic gas molecules (CO, NO, CO2, NH3, and NO2) on 12 – borophene was investigated by first – principle calculations using three van der Waals correlation functionals: revPBE-vdW, optPBE-vdW, and vdW-DF2. The most stable configurations and diffusion possibilities of the gas molecules on the 12 – borophene surface were determined visually by using Computational DFT-based Nanoscope [10]. The nature of bonding and interaction between gas molecules and 12 – borophene are also disclosed by using the density of states analysis and Bader charge analysis. The obtained results are not only considerable for understanding gas molecules on borophene but also useful for technological applications of borophene in very near future